1988
DOI: 10.1016/0014-5793(88)81371-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of maitotoxin on ATP secretion and on phosphoinositide breakdown in rat pheochromocytoma cells

Abstract: Maitotoxin (MTX) induced exocytotic secretion of ATP from PCI2 rat pheochromocytoma cells. The threshold for stimulation of secretion was at concentrations of about 2 ng/ml of MTX. Maximal release occurred at 40 ng/ml. MTX-induced ATP release required the presence of calcium in the extracellular medium and could be inhibited by nifedipine, a specific blocker of voltage-dependent calcium channels. In addition to the effects on ATP secretion from PCI2 cells, MTX stimulated the breakdown of phosphoinositides, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…From these results it was concluded that both P-CTX-1 and bradykinin might elevate intracellular Ca 2+ through the same InsP 3 -sensitive Ca 2+ stores in nerve cells [ 104 ]. Past experimentation on synaptosomes [ 160 162 ] and cardiac myocytes [ 163 ] has also revealed that any enhanced influx of Na + stimulates the production of InsP 3 , presumably through the activation of phospholipase C. A Na + -dependent mobilization of Ca 2+ from InsP 3 -sensitive stores could explain the increase in asynchronous quantal neurotransmitter release from motor nerve terminals that have been exposed to P-CTX-1 in a Ca 2+ -free bath solution [ 103 , 106 ]. More recently P-CTX-1 has been shown to cause a transient increase in intracellular InsP 3 mass levels in rat myotubes, an action that was blocked by TTX [ 142 ].…”
Section: Other Na + -Dependent Actions Of Ciguatoxinmentioning
confidence: 99%
“…From these results it was concluded that both P-CTX-1 and bradykinin might elevate intracellular Ca 2+ through the same InsP 3 -sensitive Ca 2+ stores in nerve cells [ 104 ]. Past experimentation on synaptosomes [ 160 162 ] and cardiac myocytes [ 163 ] has also revealed that any enhanced influx of Na + stimulates the production of InsP 3 , presumably through the activation of phospholipase C. A Na + -dependent mobilization of Ca 2+ from InsP 3 -sensitive stores could explain the increase in asynchronous quantal neurotransmitter release from motor nerve terminals that have been exposed to P-CTX-1 in a Ca 2+ -free bath solution [ 103 , 106 ]. More recently P-CTX-1 has been shown to cause a transient increase in intracellular InsP 3 mass levels in rat myotubes, an action that was blocked by TTX [ 142 ].…”
Section: Other Na + -Dependent Actions Of Ciguatoxinmentioning
confidence: 99%
“…Extracellular ATP (exATP) and exADO are accepted biochemical markers of cancer, due to their significant levels in the tumor interstitium. ATP release by cancer cells and the subsequent activation of purinergic receptors and intracellular pathways have been reported in various cancer models, such as pheochromocytoma PC-12 cells stimulated with maitotoxin [13]; Ehrlich ascites tumor cells, ATP release induced by mechanical stimulation [14]; A549 human lung cancer cells, by exocytosis triggered by TGF-β stimulation [15]; SKOV-3 ovarian carcinoma-derived cells released by a pipette generated flux [16]; I-10 testicular cancer cells through pannexin-1 [17]. A breakthrough was the monitoring of ATP in vivo in a tumor-bearing mouse with the use of reporter cells carrying an extracellular ATP sensor.…”
Section: Purines In Tumor Microenvironmentmentioning
confidence: 99%
“…MTX is believed to be a powerful disruptor of Ca 2+ homeostasis, with a multiplicity of pharmacological effects upon several cell lines [ 119 ]. Its ability to trigger intracellular cascades of events—e.g., membrane depolarization in excitable cells [ 126 ], insulin [ 127 ] and neurotransmitter secretion [ 128 , 129 ], phosphounisitide breakdown (important in cell lipids and cell signaling) [ 130 ], programmed cell death [ 131 ], and fertilization [ 132 , 133 ], justify why this compound is a powerful tool for research in cell biology, namely when attempting to elucidate Ca 2+ -dependent cellular processes [ 119 ]. MTX has also been suggested to play a role in innate immune responses and inflammation in vivo [ 119 , 134 ].…”
Section: Characterization Of Main Dinoflagellate Bioactive (Potentmentioning
confidence: 99%